RANCANG BANGUN APLIKASI PENGOLAHAN DATA ADMINISTRASI PASIEN PADA RSUD KOTA PRABUMULIH BERBASIS WEB - Tika Tika; Khana Wijaya; Nur Aini H (Elkom : Jurnal Elektronika dan Komputer, 2024)
Along with the development of technology, the use of computers as a tool really needs to be used, especially in the health sector. The Prabumulih City General Hospital is the only hospital owned by the Prabumulih City Government and is a first-level referral. The patient registration process at the Prabumulih City Hospital is still direct, by means of the patient/patient's guardian coming directly to the health service facility, then the patient is given a registration queue number, then the patient waits for a call according to the queue number, after the queue number is called, the officer will ask the type of patient new or old, poly patient purposes, outpatient or inpatient care, private payments or BPJS, after that the officer enters patient data to create a queue number for patient care in order to get health services. In this regard, it is necessary to have an application system for patient administration so that new patients can register online through the internet network, making it easy for old patients to check personal data, view doctor schedules, take queues and others.